2019
DOI: 10.3390/polym11030444
|View full text |Cite
|
Sign up to set email alerts
|

Novel Chemical Cross-Linked Ionogel Based on Acrylate Terminated Hyperbranched Polymer with Superior Ionic Conductivity for High Performance Lithium-Ion Batteries

Abstract: A new family of chemical cross-linked ionogel is successfully synthesized by photopolymerization of hyperbranched aliphatic polyester with acrylate terminal groups in an ionic liquid of 1-butyl-3-methylimidazolium tetrafluoroborate (BMIMBF4). The microstructure, viscoelastic behavior, mechanical property thermal stability, and ionic conductivities of the ionogels are investigated systematically. The ionogels exhibit high mechanical strength (up to 1.6 MPa) and high mechanical stability even at temperatures up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…In general, the iongels unveil a typical rubber-like behavior, as the storage modulus (G') of the materials is above the loss modulus (G") in the whole range of temperatures studied (Figure S7), confirming a cross-linked network and the solid nature of the free-standing iongels. This behavior is in agreement with what has been reported in the literature for other UV-cross-linked iongels [31,50,51]. In addition, the storage modulus is practically constant between 10 and 100 • C for the majority of the prepared iongels, meaning that their solid-state structures are not destroyed.…”
Section: Mechanical Propertiessupporting
confidence: 91%
“…In general, the iongels unveil a typical rubber-like behavior, as the storage modulus (G') of the materials is above the loss modulus (G") in the whole range of temperatures studied (Figure S7), confirming a cross-linked network and the solid nature of the free-standing iongels. This behavior is in agreement with what has been reported in the literature for other UV-cross-linked iongels [31,50,51]. In addition, the storage modulus is practically constant between 10 and 100 • C for the majority of the prepared iongels, meaning that their solid-state structures are not destroyed.…”
Section: Mechanical Propertiessupporting
confidence: 91%
“…Hyperbranched polymers (HPs), as special and multifunctional cross-linkers, have been paid more and more attention because their special topological structures, abundant functional and controllable end groups, and low viscosity. Interestingly, Duan and co-workers reported that the hyperbranched polymers can simultaneous improve the strength and elongation of carbon nanotube films by making full use of the flexible hyperbranched structure and high cross-linking ability of the HP cross-linkers . Furthermore, our group found that some hyperbranched polymers and dendrimers can be easily dissolved in ionic liquids. , The above investigations have provided a very important way to construct 3D printable, stretchable and stable chemical ionogels by constructing novel hyperbranched polymer-centric cross-linking networks via a one-step 3D printing method.…”
Section: Introductionmentioning
confidence: 99%
“…The designed layered heterostructure IL-based gels hold high ionic conductivity of >1 mS cm −1 at room temperature. Zhao et al conducted photopolymerization to produce an IL-based gel based on hyperbranched polymer aliphatic polyester with acrylate terminal groups in BMIMBF 4 with superior ionic conductivity for the fabrication of gel polymer electrolytes for applications in lithium-ion batteries [ 45 ]. The synthesis of this IL-based gel was carried out in two stages, which are illustrated in Figure 2 a. HP-OH was obtained through a quasi-one-step reaction of 2, 2-bis(hydroxymethyl)propionic acid (DMPA), 2-ethyl-2-(hydroxymethyl)-1,3-propanediol (TMP), and a number of catalytic PTS, and then synthesized to create acrylic terminated hyperbranched polymer (HP-A).…”
Section: Preparation Of Il-based Gelmentioning
confidence: 99%
“…A used IL-based gel component is a mixture of P(VDF-HFP) poured on Pyr 13 TFSI and 0.6 g Li salt LiTFSI + 0.7 g IL Pyr 13 TFSI. In addition, the synthesis of a new family of chemically crossed IL-based gels was introduced by photopolymerization of branched aliphatic polyesters (HP-OH) with terminal acrylic groups [ 45 ]. Although quite complex, the results of this IL-based gel can achieve a mechanical strength up to 1.6 MPa, and are mechanically stable up to 200 °C, thermal up to 371.3 °C, and have an electrochemical window up to >4.3 V.…”
Section: Applications Of Il-based Gelsmentioning
confidence: 99%